On photosynthesis and polar bears (Ökologisches Wirtschaften - Fachzeitschrift, 2007)
As opposed to humankind, plants and animals rely completely on one kind of renewable energy: the sun’s solar radiation. Biomimetic concepts mimic nature’s energy system and may thus contribute to sustainability.